Studi Analisis Bibliometrik Perkembangan Penelitian Bidang Akuntansi Pemerintahan - Puteri Utami, Nadia (Jurnal Etnik: Ekonomi-Teknik, 2021)
Threats such as liquidation, competition, and profitability may be of urgent concern to private sector organizations, but are significantly less relevant in a government context. Factors that are more important for the government include long-term stability, the ability to consistently cover annual expenditures and debts, and the management of public funds, the development of accounting in the field of government has become an important role in the administration and governance of government finances so that research in the field of government accounting in recent years is indispensable. This study aims to find out how to study the development of research in the field of government accounting by conductinganalysis bibliometric to investigate references to scientific articles in the field of government accounting. The research method used is a quantitative method to analyze a literature review that summarizes and evaluates a collection of writings on a topic. Research in the field of government accounting occurred at most in 2017. Based on theanalysis bibliometric that has been carried out, research on government accounting is very necessary to meet the needs of stakeholders to assess government accountability and to make political, social, and economic decisions.